PERLINDUNGAN HUKUM TERHADAP PEGAWAI NOTARIS YANG TIDAK DIDAFTARKAN PADA PROGRAM BPJS KETENAGAKERJAAN OLEH NOTARIS DITINJAU DARI UNDANG-UNDANG NOMOR 40 TAHUN 2004 TENTANG SISTEM JAMINAN SOSIAL NASIONAL (STUDI DI KANTOR NOTARIS KOTA MEDANDAN KABUPATEN DELISERDANG) - Putrinda, Dwita Ajeng; Sinaga, Henry; Agusmidah, Agusmidah (JOURNAL OF SCIENCE AND SOCIAL RESEARCH, 2025)
Abstract: Based on article 13 number 1 of Law Number 40 of 2004 concerning the National Social Security System, namely "Employers are required to gradually register themselves and their employees as participants with the social security organizing body, in accordance with the social security program followed". However, the fact in the field is that notaries as employers are still negligent in their obligations to register their employees in the BPJS Ketenagakerjaan program, one of the social security programs created by the government to improve the welfare of workers, which means that notaries do not comply with Law Number 30 of 2014 concerning the Regulation of Notary Positions Article 4 Number 1. The results of this study indicate that the reason notaries do not register their workers is due to the lack of knowledge about social security and the factor of administrative sanctions that are not firm and the lack of supervision of protection for workers who have been registered or have not been registered. then also notaries who do not care about the welfare of their workers. The suggestions in this study are as follows: Notaries are expected to submit to and comply with the SJSN Law which states that notaries are employers, and based on the SJSN Law and the BPJS Law, employers are required to register their employees in the BPJS Employment program, secondly, the sanctions for notaries who have not fulfilled social security for their employees are still too light so that they do not have a deterrent effect, thirdly, it is expected that notaries and their employees are active and continue to synergize in implementing applicable laws and regulations for the sake of mutual progress and prosperity. Keyword: Social Security, Notary Employees, BPJS Employment Abstrak: Berdasarkan pasal 13 angka 1 Undang-Undang Nomor 40 Tahun 2004 tentang Sistem Jaminan Sosial Nasional yaitu “Pemberi kerja secara bertahap wajib mendaftarkan dirinya dan pekerjanya sebagai peserta kepada badan penyelenggara jaminan sosial, sesuai dengan program jaminan sosial yang diikuti”. Namun fakta dilapangan notaris sebagai pemberi kerja masih lalai akan kewajibannya untuk mendaftarkan pegawainya pada program BPJS Ketenagakerjaan salah satu program jaminan sosial yang dibuat pemerintah untuk mensejahterakan pekerja yang berarti notaris tidak patuh terhadap Undang-Undang Nomor 30 Tahun 2014 Tentang Peraturan Jabatan Notaris Pasal 4 Angka 1. Hasil penelitian ini menunjukan penyebab notaris tidak mendaftarkan pekerjanya karena minimnya pengetahuan tentang jaminan sosial serta faktor tidak tegasnya sanksi administratif dan kurangnya pengawasan terhadap perlindungan pada tenaga kerja yang sudah didaftarkan ataupun yang belum didaftarkan. kemudian juga notaris yang kurang memperdulikan kesejahteraan pekerjanya. Saran dalam penelitian ini adalah sebagai berikut Notaris diharapkan tunduk dan mematuhi UU SJSN yang menyatakan bahwa notaris merupakan pemberi kerja, dan berdasarkan UU SJSN dan UU BPJS pemberi kerja wajib mendaftarkan karyawannya pada program BPJS Ketenagakerjaan, kedua sanksi bagi notaris yang belum memenuhi jaminan sosial untuk pegawainya masih terlalu ringan sehingga tidak menimbulkan efek jera, ketiga Diharapkan notaris dan karyawannya aktif dan terus bersinergi dalam penerapan peraturan perundangan-undangan yang berlaku demi kemajuan dan kesejahteraan bersama. Kata kunci: Jaminan Sosial, Kesejahteraan, BPJS Ketenagakerjaan